Efektivitas Problem Based Learning Terhadap Literasi Matematika Siswa Introvert dan Ekstrovert - Murwaningtyas, Chatarina Enny; Ayuwanditya, Caecillia Berta (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to evaluate the effectiveness of problem-based learning in improving mathematical literacy, particularly in statistics, in classes dominated by introverted and extroverted students. The research employs a mixed-methods approach, combining quantitative and qualitative analysis, conducted at a private high school in Bogor. Data were collected through pretests and posttests to measure learning improvements, as well as observations during the learning process to examine interactions and student responses. The results showed that the implementation of problem-based learning significantly enhanced mathematical literacy in both classes. Although there were variations in interaction dynamics based on students' personality types, no significant difference was found in learning improvement between the introverted and extroverted classes. These findings indicate that problem-based learning can be effectively implemented for students with different personality types.  Keywords: Problem Based Learning, Mathematical Literacy, Introvert, Extrovert.